Social web and libraries - Kelly, Brian (Henry Stewart Talks, 2012)
History of the web, Web 1.0, Web 2.0, Social web, Social networks, Redefining 'social', Library uses, Social web technologies, Blogs, Twitter, Challenges, Futures